Attending to Nuanced Emotions: Fostering Supervisees' Emotional Awareness and Complexity. (March 2017) - Tangen, Jodi L.
Abstract : There is limited supervision research exploring how supervisees learn emotional awareness and complexity. In this article, the 5 levels of emotional awareness and 3 aspects of emotional complexity are explored in light of the supervision enterprise. In addition, 2 supervision intervention guides and a case example are provided.